PENANAMAN NILAI NILAI AGAMA ISLAM PADA ANAK USIA DINI DI RA PERWANIDA JATIWATES TEMBELANG - Zahrotul Muniroh (Universitas KH. A. Wahab Hasbullah, 2020)
This study aims to describe: 1) the inculcation of Islamic religious values ​​in early childhood in RA PERWANIDA JATIWATES, 2) How the method of inculcating Islamic religious values ​​in early childhood, 3) What are the supporting factors and obstacles to the inculcation of religious values Islam in early childhood. The results showed that: 1) The inculcation of Islamic religious values ​​in early childhood includes planning, implementation and evaluation. The planning includes the preparation of a Syllabus, RPT, RPB, RPM and RKH. Implementation has several stages of activities including opening activities, core activities, breaks and closing activities. 2) Methods of inculcating Islamic religious values ​​in early childhood, namely by using the habituation method, exemplary method, demonstration method, question and answer method, 3) Supporting factors among others, educators are experts and professionals, facilities and infrastructure, the availability of learning media, the condition of children who are enthusiastic and ready to learn. While the inhibiting factors include: Family background Potential, motivation, enthusiasm, seriousness, There are children who are active, Children are difficult to tidy up and return the game, There are students who are easily bored, There are educators who have limitations in operating the computer, the circumstances of parents who do not all provide further education to guide and habituate children when at home.